Microplastic Occurrence in the Gastrointestinal Tract of a Risso’s Dolphin Grampus griseus in the Northeastern Mediterranean Sea - Nebil Yücel; Ece Kılıç; Cemal Turan; Sefa Ayhan Demirhan (Aquatic Sciences and Engineering)
Risso’s dolphin Grampus griseus was stranded on the coast of Arsuz-Uluçınar, Iskenderun Bay, Turkey in the northeastern Mediterranean on 29 March 2022. This study was conducted to reveal the relationship between G. griseus and microplastic debris in the northeastern Mediterranean Sea. The gastrointestinal tract (GIT) of one stranding G. griseus was examined, and 454 microplastics particles were extracted. Of all, the majority of them were fibers (96%), black in colour (62%), and 0.5-1 mm in size (38%). This paper represents the first data indicating the microplastic abundance in G. griseus from the northeastern Mediterranean Sea. Also, it creates a baseline to understand the relationship between cetaceans and microplastics in this region.